Histopathological, immunohistochemical and biomolecular diagnosis of myocarditis due to Clostridium chauvoei in a bovine - Casagrande,Renata Assis (2015)
The aim of this study was to report a case of clostridial myocarditis in a bovine in Brazil with emphasis on the pathological findings, isolation and molecular identification associated with the in situ localization of C. chauvoei. The animal, a male Brangus bull with nine months of age, was found dead without prior clinical signs. Multifocal and coalescent areas of necrosis were observed in the myocardium. Rod cells in the cardiac muscle fibers were positive immunostaining for C. chauvoei, while this bacterium was also isolated and identified by polymerase chain reaction (PCR).